The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10826084.2016.1271985
|View full text |Cite
|
Sign up to set email alerts
|

College-Related Alcohol Beliefs and Problematic Alcohol Consumption: Alcohol Protective Behavioral Strategies as a Mediator

Abstract: Background College-related alcohol beliefs, or beliefs that drinking alcohol is central to the college experience, have been shown to robustly predict alcohol-related outcomes among college students. Given the strength of the associations, it is imperative to understand more proximal factors (i.e., closer in causal chain leading to alcohol-related outcomes) that can explain these associations. Objectives The current research examined alcohol protective behavioral strategies (PBS) as a potential mediator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Challenging these risky cognitions in prevention programs and wellness classes as well as introducing protective behavioral strategies (Bravo, Prince, & Pearson, 2017) can decrease alcohol consumption and drinking problems among college students of diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Challenging these risky cognitions in prevention programs and wellness classes as well as introducing protective behavioral strategies (Bravo, Prince, & Pearson, 2017) can decrease alcohol consumption and drinking problems among college students of diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using the CLASS, researchers have found that men endorse higher college alcohol beliefs compared to women (Bravo et al, 2017;Hustad et al, 2014;Pearson and Hustad, 2014). To date, it is unclear whether these findings regarding sex and college perceptions reflect actual differences in the degree to which men and women hold these perceptions, or whether they instead reflect measurement bias in the measure itself.…”
Section: Introductionmentioning
confidence: 95%
“…Participants were college students recruited from four universities across three countries to participate in an online survey regarding personal mental health, personality traits, and alcohol use behaviors (see Bravo, Pearson et al, 2017 for more information on recruitment procedures).…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies are classified into three subtypes: serious harm reduction (PBS-SHR; using a designated driver), stopping/limiting drinking (PBS-SLD; leaving the bar/party at a predetermined time), and manner of drinking (PBS-MOD; drink slowly versus chugging or gulping). Generally, evidence supports the protective value of PBS (Pearson, 2013); however, different effects can be found when PBS are dismantled into their subtypes (Bravo, Prince, & Pearson, 2017). It appears that PBS-SLD and PBS-MOD tend to vary in their negative association with alcohol consumption while PBS-SHR tends to be linked with decreases in ARNC (Napper, Kenney, Lac, Lewis, & LaBrie, 2014;Pearson, 2013).…”
Section: Introductionmentioning
confidence: 99%